The optimization and characterization of dairy-based agglomerated protein products using whey protein hydrolysate as a binding agent - Zaitoun, Baheeja Jameel (Kansas State University, 2020)
Whey proteins are highly soluble and have many functions in food applications such as gelation, foaming, and emulsification. Many approaches were performed to modify the physiochemical characteristics of whey proteins such as enzymatic hydrolysis. The type and specificity of the enzyme influence the properties of the resultant hydrolysate. In a recent disclosure of invention, whey protein hydrolysate (WPH) was utilized as a binder in whey protein isolate (WPI) wet agglomeration process. The first objective of this study was to characterize the physical and chemical properties of three lots of commercial WPH. High-performance liquid chromatography (HPLC) and Matrix Assisted Laser Desorption/Ionization- Time of Flight (MALDI-TOF) confirmed a complete hydrolysis of whey proteins in the three lots, which indicated a consistent hydrolysis. Moreover, the degree of hydrolysis was not significantly different (P>0.05) among the lots. The second objective of the study was to optimize and evaluate the effectiveness of WPH as a binder in wet agglomeration of WPI. The second objective was carried out in two phases. In the first phase, a 3×3×2 factorial design was conducted with pre-wet mass (60, 100, and 140 g), WPH concentration (15, 20, and 25%), and flow rate (4.0 and 5.6 mL.min⁻¹) as independent variables, and the other processing parameters were kept constant. Agglomeration was carried out in a top-spray fluid bed granulator (Midi-Glatt, Germany). All the experiments were performed in triplicates and agglomerated WPI samples were stored at 25°C. In the second phase, agglomerated WPI samples were analyzed for functional and physical characteristics such as moisture content, water activity, emulsifying capacity, the agglomerates size and shape characteristics, and density. Moisture content of agglomerated samples was within the range of 3 – 15%. The treatment combinations of high pre-wet mass (140g) and flow rate (5.6 mL.min⁻¹) resulted in high moisture content and water activity in the agglomerated WPI samples, consequently, clumps were formed during the agglomeration process. The size and shape characteristics of agglomerates were evaluated using Morphology G3-ID (Malvern Instruments Ltd, UK). The mean of circle equivalent diameter (CED), circularity, elongation, and convexity were measured. The CED of the WPI agglomerates was in between 13.63-17.96 µm. No significant differences (P>0.05) were observed for the CED and convexity for the main effects and their interaction. The utilization of WPH as a binder is a promising approach to produce “lecithin free” agglomerated high protein powders, which provides a product with a clean label. In addition, the shelf life of agglomerated powders can be increased as WPH is not susceptible to oxidation as lecithin. Overall, the results suggest that WPH may be used as an alternative of soy lecithin in agglomerating WPI.
Keywords: Agglomeration; Whey; Isolate; Hydrolysate; Binder